Design, Synthesis and Characterization of a Bicompartmental bisthiosemicarbazone Ligand - Isabel Velo-Heleno; Sandra Fernández-Fariña; Uxía Barreiro-Sisto; Laura Rodríguez-Silva; Rosa Pedrido (Chemistry Proceedings)
In this work, we present the design and synthesis of the bisthiosemicarbazone ligand H3LMe by means of an iminic condensation reaction between 2-hydroxyisophthalaldehyde and 4-methyl-3-thiosemicarbazide. This ligand is bicompartmental, pentadentate [N2S2O] and potentially trianionic. The presence of a spacer constituted by a phenol group facilitates the coordination of transition metal ions, giving rise to a great variety of structures. To confirm the purity of the ligand, different characterization techniques were employed, including elemental analysis, mass spectrometry, infrared spectroscopy, and nuclear magnetic resonance. The acquisition of suitable crystals of H3LMe allowed us to analyze its structure through X-ray diffraction studies.